Light absorption budget in a reservoir cascade system withwidely differing optical properties - Bernardo, Nariane [UNESP] (2019)
Aquatic systems are complex systems due to the environmental pressures that lead to water quality parameter changes, and consequently, variations in optically active compounds (OAC). In cascading reservoir systems, such as the Tietê Cascade Reservoir System (TCSR), which has a length of 1100 km, the horizontal gradients are expressive due to the filtration process that is caused by the sequence of dams affecting the light absorption throughout the cascade. Our new observations showed that colored dissolved organic matter (CDOM) dominate two reservoirs; non-algae particles (NAP) dominate one, and phytoplankton dominates the other. The variability of light absorption along the cascade indicates the influence of watershed dynamics in the reservoirs as much as the flow driven by previous reservoirs. Despite the effect of the variability of light absorption, light absorption by phytoplankton strongly affects the total absorption in the four reservoirs in TCSR. The results obtained in this work may enable a better understanding of how the gradient pattern changes primary production and indicates a challenge in retrieving OAC concentrations using a bio-optical model for an entire cascade composed of different optical environments.